Flexural Behavior of Two-Way Slabs Reinforced Using Welded Wire Mesh - Rasha Mabrouk; El-Sayed Ewida; Nasser El-Shafey; Akram Torkey (Journal of Engineering Research - Egypt, 2022)
This paper is the second part of a research program that studies the behavior of concrete solid slabs reinforced using welded wire mesh and the effectiveness of using welded wire meshes as an economic replacement to ordinary steel bars. This paper focuses on two-way solid slabs where nine two-way simple specimens were tested using concentrated, line, and uniform loading setup. The parameters studied were the effect of using welded mesh and the number of layers utilized. Following that, a finite element analysis using the ABAQUS 6.13 program was conducted. Comparison between the experimental and analytical results showed good correlation. The results showed that the number of layers of welded metal-mesh and load type have a significant effect on the capacity of the slabs. The specimens with welded wire mesh showed higher capacities than that with ordinary reinforcing bars as well as an enhanced cracking behavior and improved ductility. A correction factor is introduced to take the effect of the welding of the wire mesh on the behavior of the concrete slabs. A comprehensive parametric study using 432 slabs was done to investigate the effects of the slab geometry, reinforcement arrangement and the concrete compressive strength. Based on the parametric study, simplified design charts were proposed which can be used as a base for the design of solid slabs reinforced using welded wire mesh.